Dearomatization of (hetero)arenes through photodriven interplay between polysulfide anions and formate - Tan, Eugene Yew Kun (2023)
The facile construction of C(sp3 )-rich carbo- and heterocyclic compounds is a pivotal synthetic strategy to foster contemporary drug discovery programs. The downstream dearomatization of readily accessible two-dimensional (2D) planar arenes represents a direct pathway towards accessing three-dimensional (3D) aliphatic scaffolds. Here, we demonstrate that polysulfide anions are capable of catalyzing a dearomatization process of substituted naphthalenes, indoles, and other related heteroaromatic compounds in the presence of potassium formate and methanol under visible light irradiation. The developed protocol exhibits broad functional group tolerance, operational simplicity, scalability, and cost-effectiveness, representing a practical and sustainable synthetic tool for the arene dearomatization.